Social Media as a Means Of Increasing Micro Small Medium Enterprises Revenue in the Era of the Covid Pandemic 19 - Amani, Tatik; Elly, Moh. Iskak; Astutik, Silvia Dwi; Hidayah, Dina Nirmala; Aliyanty, Noviana; Mardiah, Holifatul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Andyla Snack Kampung is an micro small and medium enterprises (MSME) actor who still does business with conventional marketing so that the marketing reach is less broad and when the Covid-19 pandemic hits it causes income to decrease because consumers are constrained by the ordering system which has to go to the MSME place or via WhatsApp with limited consumers who know the cellphone number MSME. We are devotees trying to help Andyla Jajanan Kampung MSME with digital marketing so that the marketing reach is wider and followed by an increase in income. The implementation method in service is mentoring, socializing and training on the use of social media as a means of online product marketing. The results of the training and mentoring activities are partners have a strong will to develop business by utilizing social media, have logos, brochures and accounts on social media facebook, youtube and instagram and can manage these media as a means of promotion. This makes Andyla Jajanan Kampung Micro, Small and Medium Enterprises which originally used an offline marketing strategy to become an online strategy (Digital Marketing) so that it has a wide reach which leads to an increase in income.